2007
DOI: 10.1152/ajpcell.00506.2006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of the mouse IGF-I exon 1 promoter region by calcineurin activation of NFAT in skeletal muscle

Abstract: Skeletal muscle development and growth are regulated through multiple signaling pathways that include insulin-like growth factor I (IGF-I) and calcineurin activation of nuclear factor of activated T cell (NFAT) transcription factors. The developmental regulation and molecular mechanisms that control IGF-I gene expression in murine embryos and in differentiating C2C12 skeletal myocytes were examined. IGF-I is expressed in developing skeletal muscle, and its embryonic expression is significantly reduced in embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…2 F), we concluded that calcineurin activity in AIC astrocytes was regulated by Dox in vivo and in vitro. That calcineurin activity is regulated by Dox was indirectly confirmed by the observation that Dox regulated the release by AIC astrocytes of humoral neuroprotective signals such as Cu/Zn SOD or IGF-I that are known to be functionally associated with calcineurin (Tokheim and Martin, 2006;Alfieri et al, 2007). Thus, in response to proinflammatory challenge with LPS, AIC astrocytes secreted larger amounts of SOD and IGF-I when cultured without Dox (Fig.…”
Section: Astrocyte Calcineurin Protects Against Brain Inflammatory Inmentioning
confidence: 76%
“…2 F), we concluded that calcineurin activity in AIC astrocytes was regulated by Dox in vivo and in vitro. That calcineurin activity is regulated by Dox was indirectly confirmed by the observation that Dox regulated the release by AIC astrocytes of humoral neuroprotective signals such as Cu/Zn SOD or IGF-I that are known to be functionally associated with calcineurin (Tokheim and Martin, 2006;Alfieri et al, 2007). Thus, in response to proinflammatory challenge with LPS, AIC astrocytes secreted larger amounts of SOD and IGF-I when cultured without Dox (Fig.…”
Section: Astrocyte Calcineurin Protects Against Brain Inflammatory Inmentioning
confidence: 76%
“…Indeed, there is a striking parallel between the observed effects of caNFATc1 in promoting the autocrine growth factor-mediated transforming pathway in murine fibroblasts that we describe here, and the well-established functional role of endogenous NFAT proteins in promoting T lymphocyte growth during the immune response via the autocrine production of the primary T lymphocyte growth factor, interleukin-2 [Rao et al, 1997;Macian, 2005]. Moreover, NFAT binding sites are present in the promoter regions of numerous cytokines and growth factor genes and the activation of the NFAT signaling pathway has been implicated in the expression of an array of secreted factors, many of which are known to act in an autocrine fashion [Rao et al, 1997;Boss et al, 1998;Abbott et al, 2000;Hogan et al, 2003;Yang and Chow, 2003;Reinhold et al, 2004;Alfieri et al, 2007]. Hence, it is tempting to speculate that the increased expression and subsequent autocrine action of growth promoting cytokines and growth factors maybe a common mechanism by which deregulated NFAT activity is able to contribute towards initial tumor growth and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin can regulate myoblast differentiation (1), transcription and/or activation of myoregulatory and growth factors [e.g., myocyte enhancer factor 2A (MEF-2A), MyoD, myogenin, and insulinlike growth factor I] (2,13,60), fusion of myoblasts to nascent myofibers (8), and expression of the developmental MyHC isoform (39). In hindlimb muscles of young mdx mice, pharmacological inhibition of calcineurin increased degeneration, impaired regeneration, and compromised muscle force-producing capacity, effects that appear to be dose dependent (49).…”
mentioning
confidence: 99%